2015
DOI: 10.1007/s12672-015-0224-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Urinary Steroid Profiling in the Evaluation of Adrenal Tumors

Abstract: Radiological examination may unexpectedly reveal an adrenal mass. Current algorithms for differentiating between benign and malignant lesions mainly rely on size and densitometry on unenhanced CT, which have limited specificity. We examined the diagnostic value of urinary steroid profiling by gas chromatography/mass-spectrometry (GC/MS) in differentiating between benign and malignant adrenal tumors. A retrospective study in two referral centers for patients with adrenal disease was performed. All urinary stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 22 publications
3
64
0
12
Order By: Relevance
“…Analysis of steroid hormones by gas chromatography mass spectrometry (GC-MS) in urine samples is a useful tool for the diagnosis of steroid synthesis disorders such as congenital adrenal hyperplasia (25,26,27,28) and P450 oxidoreductase deficiency (27,29). It has also been successfully applied for the discrimination between benign and malignant adrenal masses (14,30,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of steroid hormones by gas chromatography mass spectrometry (GC-MS) in urine samples is a useful tool for the diagnosis of steroid synthesis disorders such as congenital adrenal hyperplasia (25,26,27,28) and P450 oxidoreductase deficiency (27,29). It has also been successfully applied for the discrimination between benign and malignant adrenal masses (14,30,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Some decades ago, it has already been considered to exploit variabilities of steroidogenic hormone production as markers of malignancy in adrenal masses (12,13). More recently, it has been shown that steroid profiling by gas chromatography mass spectrometry (GC-MS) of urine samples collected over 24 h has diagnostic value in discriminating benign and malignant adrenocortical tumors (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, the panel acknowledges that the published evidence for this suggestion is very low (184,193). A very promising new tool to discriminate benign from malignant adrenocortical tumors appears the analysis of a comprehensive urinary steroid profile measured by GC-MS or LC-MS (194,195). (Fig.…”
Section: Reasoningmentioning
confidence: 99%
“…More recently, in a series of 102 patients with ACAs and 45 with ACCs, urinary steroid profiling differentiated ACCs from ACAs with a sensitivity and specificity of 90% (Arlt et al 2011). Kerkhofs et al (2015) showed that tetrahydro-11-deoxycortisol (THS) at a cut-off value of 2.35 mmol/24 h differentiated ACC (nZ27) from other adrenal disorders (nZ125) with a sensitivity of 100% and specificity of 99%.…”
Section: Geneticsmentioning
confidence: 99%